First correct Experimental Discovery of "Weak Gyrotropy" of Transparent Non-Centrosymmetric "Non-Gyrotropic" Crystals, Using the LiNbO3 Crystal as an Example - Zilbershtein, A. Kh. (Research Developments in Science and Technology Vol. 3, 2022)
Study objective was the correct experimental discovery of the effect of „weak“ gyrotropy of the „non-gyrotropic“ transparent non-centrosymmetric crystals. The original experiment was based on studies of the system's light transmission (T): Polarizer - wedge-shaped Crystal sample - Analyzer (orthogonal to Polarizer). It was demonstrated that: if the optical axis of the crystal is parallel to the rib of the wedge and to the polarization of the linear-polarized incident light, then the transmission T of the system can be not equal to zero (due to existence of nonzero components (G12) of the antisymmetric pseudotensor of gyration G described the „weak“ gyrotropy ). Such nonzero T was identified for the first time experimentally using the LiNbO3 crystal as an example. Absolute value of components G12 of the LiNbO3 crystal was first estimated: ([G12] = (1.50 +/- 0.51) 10-6). Subject Areas: Physics & Mathematics.